Electroacupuncture Promotes Remyelination after Cuprizone Treatment by Enhancing Myelin Debris Clearance - Zhu, Keying; Sun, Jingxian; Kang, Zheng; Zou, Zaofeng; Wu, Gencheng; Wang, Jun (Frontiers in Neuroscience, 2017)
Promoting remyelination is crucial for patients with demyelinating diseases including multiple sclerosis. However, it is still a circuitous conundrum finding a practical remyelinating therapy. Electroacupuncture (EA), originating from traditional Chinese medicine, has been widely used to treat CNS diseases all over the world, but the role of EA in demyelinating diseases is barely known. In this study, we examined the remyelinating properties and mechanisms of EA in cuprizone-induced demyelinating model, a CNS demyelinating murine model of multiple sclerosis. By feeding C57BL/6 mice with chow containing 0.2% cuprizone for 5 weeks, we successfully induce demyelination as proved by weight change, beam test, pole test, histomorphology and Western Blot. EA treatment significantly improves the neurobehavioral performance at week 7 (2 weeks after withdrawing cuprizone chow). RNA-seq and RT-PCR results reveal up-regulated expression of myelin-related genes, and the expression of myelin associated protein (MBP, CNPase, and O4) are also increased after EA treatment, indicating therapeutic effect of EA on cuprizone model. It is widely acknowledged that microglia exert phagocytic effect on degraded myelin debris and clear these detrimental debris, which is a necessary process for subsequent remyelination. We found the remyelinating effect of EA is associated with enhanced clearance of degraded myelin debris as detected by dMBP staining and red oil O staining. Our further studies suggest that more microglia assemble in demyelinating area (corpus callosum) during the process of EA treatment, and cells inside corpus callosum are mostly in a plump, ameboid and phagocytic shape, quite different from the ramified cells outside corpus callosum. RNA-seq result also unravels that most genes relating to positive regulation of phagocytosis (GO:0050766) are up-regulated, indicating enhanced phagocytic process after EA treatment. During the process of myelin debris clearance, microglia tend to change their phenotype toward M2 phenotype. Thus, we also probed into the phenotype of microglia in our study. Immuno-staining results show increased expression of CD206 and Arg1, and the ratio of CD206/CD16/32 are also higher in EA group. In conclusion, these results demonstrate for the first time that EA enhances myelin debris removal from activated microglia after demyelination, and promotes remyelination.